2015
DOI: 10.1016/j.ijimpeng.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of shock front propagation in the density graded cellular rods

Abstract: The present theoretical study focuses on the shock front propagation in a density graded cellular rod. It aims at the determination of the shock front velocity evolution as well as the stress evolution during the impact. The density gradient leads necessarily to the property gradient, which is taken into account in this analysis. The locking strain in classical shock front theory is replaced by the notion of the locking density to adapt to the studied case. Analytical solutions of linear, quadratic and square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…In the numerical simulations, the authors used an aluminium based foam material with notable strain hardening for which the RPPL material approximation is not accurate. Another model for compaction of graded cellular material using also the RPPL material approximation was proposed by Liu et al (2015) where a predefined locking density was defined from which the densification strains ware obtained. Several functions for the density gradient ware analysed in this study however, the gradient always increased in the direction of the propagation of the compaction wave, which limited the observed phenomena types.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…In the numerical simulations, the authors used an aluminium based foam material with notable strain hardening for which the RPPL material approximation is not accurate. Another model for compaction of graded cellular material using also the RPPL material approximation was proposed by Liu et al (2015) where a predefined locking density was defined from which the densification strains ware obtained. Several functions for the density gradient ware analysed in this study however, the gradient always increased in the direction of the propagation of the compaction wave, which limited the observed phenomena types.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…The dynamic response of the metallic foam is critical for the design of foam-filled sandwich structures. Researches (Ajdari et al, 2009; Goetz and Matous, 2013; Hou et al, 2014; Karagiozova and Alves, 2014, 2015; Liu et al, 2015; Shen et al, 2013, 2014) have shown that the mechanical response of graded metallic foam core is superior to the uniform density core. There are two types of density-graded structure.…”
Section: Dynamic Response For the Increasing Density Arrangementmentioning
confidence: 99%
“…Results show that the gradient significantly influences the energy absorption capability. Shen et al (2014) and Liu et al (2015) proposed improved models based on the R-P-P-L model. Goetzet and Matous (2013) proposed an elastic-plastic-densifying (EPD) model to obtain the nonlinear wave equation in the two layer cellular materials.…”
Section: Introductionmentioning
confidence: 99%
“…Wang等人 [4,8] 通过变胞元技术构 建了连续密度梯度蜂窝结构的数值计算模型, Yang等 人 [14] 将其进一步拓展到了三维情形. 多种密度分布的梯度多胞材料的冲击响应和吸能 特性已经得到研究 [24,25] . 近来, Yang等人 [14] 提出了反向 设计的思想, 即在给定的冲击力下, 基于冲击波模型对 梯度多胞结构的相对密度分布进行设计, 并利用细观 有限元模型证实了有效性.…”
Section: 另一类是连续梯度 通过控制密度梯度分布函数可以unclassified